The McGraw-Hill homeland security handbook strategic guidance for a coordinated approach to effective security and emergency management - Kamien, David G. (McGraw-Hill, 2012)
Provides government officials, corporate risk managers, business and security executives, first responders, and all homeland security and emergency prepared-ness professionals with a wide-ranging and definitive overview of critical homeland security issues.